Eschatological Presence in Karl Barth’s Göttingen Theology. By Christopher Asprey - Bradshaw, Timothy (The journal of theological studies, 2011)
In 1921 Karl Barth was appointed to his first academic post, Professor of Reformed Theology at Göttingen, where he lectured until 1925 and his move to Münster. His lectures and papers from that time have now become available, and Christopher Asprey offers his readers a tightly focused reading of this theological material, notably Barth’s first attempt at dogmatic theology, Unterricht in der christlichen Religion, published in English as The Göttingen Dogmatics, written from 1924 and finished in Münster in 1926. Asprey’s book is a revised version of his Aberdeen doctoral thesis., As in all good theses, he sets out his aim early and clearly.